2010
DOI: 10.14411/fp.2010.014
|View full text |Cite
|
Sign up to set email alerts
|

Potential solutions to problems posed by the offspring sex ratios of people with parasitic and viral infections

Abstract: i have hypothesized that mammalian offspring sex ratios (proportions male at birth) are partially controlled by the hormone levels of both parents around the time of conception. recently data have been published (privately) which impugn suggestions of mine (based on that hypothesis) relating to the offspring sex ratios of people who are carriers of hepatitis B virus; and (publicly) to hormone profiles of women who are infected with the protozoan parasite Toxoplasma gondii. Here these data are reviewed in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…As a possible explanation, he suggested publication bias, that is, an initial euphoria concerning the intensity of manipulation effects became replaced by more realistic estimates over time (Poulin, 2000). More recently, other authors have stressed that alternative explanations need to be considered-and excluded-to provide conclusive empirical support for an assumed case of manipulation (Klein, 2005;Thomas et al, 2005;James, 2010;Cator et al, 2012Cator et al, , 2015Lafferty and Kuris, 2012;Worth et al, 2013). Alternatively, such alterations can: (1) represent mere side-effects of the pathology that is associated with infection; (2) form part of the successful immune response of the host to parasitization; or (3) represent traits that were inherited from ancestors but represent maladaptations in the present host-parasite combination (Klein, 2005;Thomas et al, 2005).…”
Section: Searching For General Patterns In Reports On Host Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a possible explanation, he suggested publication bias, that is, an initial euphoria concerning the intensity of manipulation effects became replaced by more realistic estimates over time (Poulin, 2000). More recently, other authors have stressed that alternative explanations need to be considered-and excluded-to provide conclusive empirical support for an assumed case of manipulation (Klein, 2005;Thomas et al, 2005;James, 2010;Cator et al, 2012Cator et al, , 2015Lafferty and Kuris, 2012;Worth et al, 2013). Alternatively, such alterations can: (1) represent mere side-effects of the pathology that is associated with infection; (2) form part of the successful immune response of the host to parasitization; or (3) represent traits that were inherited from ancestors but represent maladaptations in the present host-parasite combination (Klein, 2005;Thomas et al, 2005).…”
Section: Searching For General Patterns In Reports On Host Manipulationmentioning
confidence: 99%
“…Similarly, several different mechanisms could cause the frequently reported association of elevated levels of testosterone in males with latent toxoplasmosis (Flegr et al, 2008;Shirbazou et al, 2011). Rather than indicating an alteration that is elicited by T. gondii, high levels of testosterone could be a causal reason for infection and represent an intrinsic trait of certain individuals that: (i) causes more risktaking behavior and thereby leads to higher infection risk, or (ii) simply provides the parasite with a "preferred endocrine environment in the host" (James, 2010). Even when T. gondii can unambiguously be shown to actively enhance the levels of testosterone in its host it remains an open question whether this capacity has primarily evolved for the manipulation of host immunity, in which case it would mainly serve infection, rather than transmission.…”
Section: Alternative Explanations For Phenotypic Alterations In Parasmentioning
confidence: 99%
“…The last line shows similar partial correlation between probability of the brief psychotic disorder diagnosis and the concentration of anti-Toxoplasma antibodies. Indirect evidence also exists for increased concentration of oestrogens in the Toxoplasmainfected women (58,59). Statistically, women get infected with T. gondii later than men in the Czech Republic.…”
Section: Clinical and Demographic Features Of Psychotic Illnessmentioning
confidence: 99%
“…further incidence increase is seen in women during the peak fertility between the age of 25 and 35 (41). Kanˇkova´et al (58) and James (59) reported that infected women are more likely to produce sons than uninfected mothers and that the offspring sex ratio (proportion of males) increases with the concentration of anti-Toxoplasma antibodies in T. gondii-positive mothers. Difference in mean age of Toxoplasma infection in men and women may be one of the factors that can help to explain the gender-associated difference in onset of schizophrenia.…”
Section: Clinical and Demographic Features Of Psychotic Illnessmentioning
confidence: 99%
“…There were no significant differences in prolactin and DHEA level in these individuals. An explanation for the observed increase in the level of testosterone in latent toxoplasmosis is that individuals with high testosterone levels are more susceptible to any infection including toxoplasmosis (James, 2010). Hirsutism, acne, alopecia are clinical expressions of testosterone in women of reproductive age (Karrer-Voegeli et al, 2009).…”
Section: Discussionmentioning
confidence: 99%